2021
DOI: 10.21037/qims-20-713
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of three-dimensional measurement in the diagnosis of thoracic myelopathy caused by ossification of the ligamentum flavum

Abstract: Background: Thoracic ossification of the ligamentum flavum (OLF) is a major cause of thoracic myelopathy, which is often accompanied by multiple segmental stenosis or other degenerative spinal diseases.However, in the above situations, it is difficult to determine the exact segment responsible. The objective of this study was to analyze three-dimensional (3D) radiological parameters in order to establish a novel diagnostic method for discriminating the responsible segment in OLF-induced thoracic myelopathy, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…None of the ASRM, ESHRE-ESGE, or Congenital Uterine Malformation by Experts (CUME) has provided detailed descriptions of normal and arcuate uterus. The 3D morphological parameters can diagnose the thoracic myelopathy resulting from thoracic ossification of the ligamentum flavum more accurately than 2D morphological parameters (18). This study found that ECL, EVM, EVL, ESM, and ESL were significantly lower in arcuate uterus compared to normal uterus using the 3D measurement approach.…”
Section: Resultsmentioning
confidence: 71%
“…None of the ASRM, ESHRE-ESGE, or Congenital Uterine Malformation by Experts (CUME) has provided detailed descriptions of normal and arcuate uterus. The 3D morphological parameters can diagnose the thoracic myelopathy resulting from thoracic ossification of the ligamentum flavum more accurately than 2D morphological parameters (18). This study found that ECL, EVM, EVL, ESM, and ESL were significantly lower in arcuate uterus compared to normal uterus using the 3D measurement approach.…”
Section: Resultsmentioning
confidence: 71%
“…However, it is difficult to simultaneously assess the severity and range of compression based only on the 1D or 2D radiological parameters (14,21). Our previous study found that the 3D OR could precisely reflect the oppressive state of OLF from multiple dimensions and thus predict the clinical grade of thoracic myelopathy (14). Herein, we introduce the 3D OR to test this hypothesis and report whether it could be used as an indicator to identify DO in patients with OLF.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, we first proposed that the formation of DO was associated with the severity of OLF compression of the dura mater and the contact area of the OLF and the dura mater. However, it is difficult to simultaneously assess the severity and range of compression based only on the 1D or 2D radiological parameters (14,21). Our previous study found that the 3D OR could precisely reflect the oppressive state of OLF from multiple dimensions and thus predict the clinical grade of thoracic myelopathy (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations